1978
DOI: 10.1007/bf00385004
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxylate decarboxylation during photorespiration

Abstract: At 25° C under aerobic conditions with or without gluamate 10% of the [1-(14)C]glycollate oxidised in spinach leaf peroxisomes was released as (14)CO2. Without glutamate only 5% of the glycollate was converted to glycine, but with it over 80% of the glycollate was metabolised to glycine. CO2 release was probably not due to glycine breakdown in these preparations since glycine decarboxylase activity was not detected. Addition of either unlabelled glycine or isonicotinyl hydrazide (INH) did not reduce (14)CO2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 23 publications
1
43
0
1
Order By: Relevance
“…Glyoxylate oxidation should yield 1 mol of CO2 (from the carboxyl carbon) and 1 mol ofa C1 fragment from the methylene carbon per mol of glycolate metabolized. Grodzinski (3) suggested that this C1 fragment may react with glycine to form serine or may be further oxidized to CO2. Depending on which reaction predominated, 50 to 100%1o of the carbon in glycolate metabolized by this pathway would be released as CO2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyoxylate oxidation should yield 1 mol of CO2 (from the carboxyl carbon) and 1 mol ofa C1 fragment from the methylene carbon per mol of glycolate metabolized. Grodzinski (3) suggested that this C1 fragment may react with glycine to form serine or may be further oxidized to CO2. Depending on which reaction predominated, 50 to 100%1o of the carbon in glycolate metabolized by this pathway would be released as CO2.…”
Section: Discussionmentioning
confidence: 99%
“…H202 produced either from the glycolate oxidase reaction (2,3,15) or in the light by a Mehler reaction within the chloroplast (17) can be the oxidant (Fig. 1).…”
mentioning
confidence: 99%
“…The photorespiratory CO2 can arise either from the direct decarboxylation of glyoxylate (9,19) or during the mitochondrial oxidation of glycine to NH3, C02, and methylene tetrahydrofolate by the enzyme glycine decarboxylase. In the latter case, NAD+ is the electron acceptor and it in turn is reoxidized by the mitochondrial electron transport chain (5,17).…”
Section: Methodsmentioning
confidence: 99%
“…Glycolate formed in the Calvin cycle is converted to glyoxylate and then glycine, and two moles of glycine are converted to one mole each of serine, ammonia and C0 2 which is responsible for photorespiration and which comprises 25% of the carbon flowing through the glycolate pathway. The oxidation of glyoxylate forms one mole each of C0 2 and formate (6). However, its contribution to photorespiration has been considered to be small (8,17).…”
mentioning
confidence: 99%